SCHOOL PHYSICAL EDUCATION AND THE PERCEPTION OF STUDENTS OF SECONDARY EDUCATION (Fiep Bulletin - online, 2015)
The objective was to ascertain the perceptions of high school students about what appears to be context-Physical Education and their expectations for their classes. By expanding the research we can conclude that the high school students include physical education is important for development of quality physical activity. This study assails a survey of descriptive character. The student is motivated when the information transmitted by the physical education teacher, has some meaning to it, ie, content meets some of their needs and attracts their attention on topics of interest and current and is in congruence with the objective that we intend to achieve in the future.
Keywords: Physical Education. Perception. High school.